“Mais flores, mais flores, mais flores”: a estrutura de sociabilidade de João Apolinário e dos subversivos da Cidade do Porto (1955-1963) (Revista de História da UEG (REVHIST), 2019)
João Apolinário, an intellectual and Portuguese poet who went into exile in Brazil, was the owner of an expressive written production, both poetic and journalistic. In this article, we will discuss the sociability structure of our character during the period in which he published his poetry books in the city of Porto, Portugal, between 1955 and 1963. We will also map actors, both artists and politicians, and institutions that have protested to the current political regime. During this period, Portugal was under the rule of Estado Novo, a regime with fascist tendencies that had strong mechanisms of censorship and political persecution. Against the backdrop of hegemonic ideology, the protagonist of our article devoted much of his poetic work to exposing his discontent with the regime and the course of Western capitalist civilization. In this sense, his sociability structure was also based on the struggle against the mechanisms of the Estado Novo, sometimes through political and partisan confrontation, starting with artistic engagement. Thus, in order to achieve our objective of analyzing this structure of sociability, we will approach Apolinario's poetry books published during this period and, due to the lack of studies on this subject, we will also use other sources such as periodicals and missives.